PERANAN PERENCANAAN ANGGARAN DALAM PENINGKATAN PEMBANGUNAN DI KABUPATEN PINRANG - Ridwan, Muh.; Hatta, Muhammad; Nur, Muhammad (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Abstract This study aims to understand the role of budget planning in enhancing development in Pinrang Regency. The research employs a qualitative descriptive method. Data collection techniques include data reduction, data presentation, data interpretation, and conclusion drawing. The subjects of this study are employees at the Regional Development Planning Agency (BAPPEDA) of Pinrang Regency who are knowledgeable about budget planning and regional development enhancement. The results of the study indicate that the government's budget or Regional Budget (APBD) plays a crucial role in planning and controlling development, serving as a guide in planning and managing local government development programs. This is evident in the process of program and budget formulation carried out by the Pinrang Regency government using a bottom-up system approach, which begins with program and budget planning from the lowest level of government structure, namely the village, up to the highest level, the regency government.